Effects of duty cycle on microstructure and iodine-induced stress corrosion cracking behavior of pulse electro-deposited zirconium coating. Issue 5 (4th May 2022) - Li, Yusha; Zhang, Yingchun; Li, Guangbin; Dong, Xiaoxu; Wang, Ying; Gu, Zongxing
ABSTRACT: Compact and dense zirconium coatings with silvery-white metallic luster were deposited on the surfaces of alloy ZIRLO under different duty cycles of 20%, 50% and 80% by pulse electro-deposition (PED) method in FLiNaK molten salt at 1023 K. The characteristics of the Zr coatings were investigated by SEM, EDS and XRD. The iodine-induced stress corrosion cracking(I-SCC) behavior of the Zr-coated alloy ZIRLO was investigated using slow strain rate tensile (SSRT) tests. The results showed that as the duty cycle increased from 20% to 80%, the average grain size of zirconium deposits increased but current efficiency decreased progressively. All of the Zr-coated samples improve the ultimate tensile strength and ductility in iodized butanol solution with respect to the uncoated Zr. The sample with Zr coating of 50% duty cycle has the highest ultimate tensile strength and ductility during the SSRT test in iodized butanol solution.